Pengaruh Keterlibatan Pelanggan dan E-commerce terhadap Kinerja UMKM di Jepara dengan Inovasi Produk sebagai Variabel Intervening - Ilma Nafia; Nurul Komaryatin (LPPM Institut Pendidikan Nusantara Global, 2026)
MSMEs face challenges in improving business performance amid increasingly fierce competition and shifts in consumer behavior in the digital era. Low customer engagement and suboptimal e-commerce use remain key constraints on leveraging digital opportunities. This study aims to analyze the effects of customer engagement and e-commerce utilization on MSME performance, with product innovation as a mediating variable. A quantitative approach was employed using a survey method, with data collected through questionnaires distributed to MSME owners in Jepara Regency. A total of 140 respondents were selected using purposive sampling, and the data were analyzed using Structural Equation Modeling (SEM) with SmartPLS version 4.0. The results indicate that customer engagement and e-commerce utilization have significant positive effects on product innovation and MSME performance. E-commerce shows a strong direct effect on product innovation (β = 0.589, p < 0.001) and MSME performance (β = 0.409, p < 0.001), while customer engagement significantly influences product innovation (β = 0.484, p < 0.001) and performance (β = 0.566, p < 0.001). Product innovation is also proven to mediate the relationship between customer engagement and MSME performance as well as between e-commerce and MSME performance. The model explains 67.8% of the variance in product innovation (R² = 0.678) and 59.4% of the variance in MSME performance (R² = 0.594), indicating a moderate to strong explanatory power. These findings highlight the importance of strengthening digital customer engagement strategies and optimizing e-commerce utilization to enhance innovation and improve MSME performance sustainably.